Ekstrak Etanol Kulit Buah Jengkol Menurunkan Kadar Glukosa dan Meningkatkan Hormon Insulin Tikus Diabetes Yang Diinduksi Streptozotocin - Malini, Desak Made; Madihah, Madihah; Khoirunnisa, Dita Aprila; Sasmita, Indriani; Ratningsih, Nining; Alipin, Kartiawati; Hermawan, Wawan (Jurnal Veteriner; Vol 20 No 1 (2019), 2019)
Diabetes Mellitus (DM) is a disease with metabolism disorder signed by increasing of glucose blood (hyperglicemia), caused by disorder of insulin secretion and or increasing of insulin resistance. Therapy of jengkol’s fruit peel is an alternative treatment for DM. This study aims to determine the effect of ethanol extract of jengkol’s fruit peel to decrease glucose and increase insulin level of Wistar female rats which induced by streptozotocin (STZ). This research used the experimental method of Completely Randomized Design (RAL). Rat were first induced by single intravenous injection of STZ except Negative Control. Furthermore, rats were divided into six groups, namely Negative Control (NC), Positive Control (PC), Reference Group (RG) glibenclamide 10 mg/kg BW, and ethanol extract of jengkol’s fruit peel (EEOJFP) treatment at dose of 385 (P1), 770 (P2), and 1540 (P3) mg/kg BW with four replications each. Treatment was administered orally for 14 days. Data were analyzed by analysis of variance (ANAVA) with 95% confidence level and Duncan Multiple Range Test. The result showed that treatment of EEOJFP with dose of 385, 770 and 1540 mg/ kgBW decreased blood glucose 28.6%;65.4% and 59.1% successively, increased insulin as 54%; 230% and 206%. There was a protective effect of EEOJEF to level of blood glucose and insulin secretion of rat-STZ induced. The conclusion from this research is Ethanol extract of Jengkol’s fruit peel at dose 770 mg/kg BW is an effective dose in decreasing the level of glucose and increasing the level of insulin hormone in STZinduced diabetic rats.